Structure Diversity and Properties of Some Bola-like Natural Products - Valentin A. Stonik; Tatyana N. Makarieva; Larisa K. Shubina; Alla G. Guzii; Natalia V. Ivanchina (Marine Drugs)
In their shapes, molecules of some bipolar metabolites resemble the so-called bola, a hunting weapon of the South American inhabitants, consisting of two heavy balls connected to each other by a long flexible cord. Herein, we discuss the structures and properties of these natural products (bola-like compounds or bolaamphiphiles), containing two polar terminal fragments and a non-polar chain (or chains) between them, from archaea, bacteria, and marine invertebrates. Additional modifications of core compounds of this class, for example, interchain and intrachain cyclization, hydroxylation, methylation, etc., expand the number of known metabolites of this type, providing their great structural variety. Isolation of such complex compounds individually is problematic, since they usually exist as mixtures of regioisomers and stereoisomers, that are very difficult to be separated. The main approaches to the study of their structures combine various methods of HPLC/MS or GC/MS, 2D-NMR experiments and organic synthesis. The recent identification of new enzymes, taking part in their biosynthesis and metabolism, made it possible to understand molecular aspects of their origination and some features of evolution during geological times. The promising properties of these metabolites, such as their ability to self-assemble and stabilize biological or artificial membranes, and biological activities, attract additional attention to them.